2019
DOI: 10.1002/bimj.201900016
|View full text |Cite
|
Sign up to set email alerts
|

Segmented Bayesian calibration approach for estimating age in forensic science

Abstract: Forensic age estimation is receiving growing attention from researchers in the last few years. Accurate estimates of age are needed both for identifying real age in individuals without any identity document and assessing it for human remains. The methods applied in such context are mostly based on radiological analysis of some anatomical districts and entail the use of a regression model. However, estimating chronological age by regression models leads to overestimated ages in younger subjects and underestimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For example, Rynkiewicz et al [19] reported an average accuracy of ±3.5 years using a wrist bone maturation method, while Chen et al [20] reported an average accuracy of ±3.7 years using a combination of dental and wrist bone maturation. Finally, this paper extends to two indices the methodology proposed in Bucci et al [8], where the best-performing method exhibited an accuracy of ±2.8 years. These findings suggest that the model developed in our study is a promising tool for accurately estimating chronological age in children and adolescents.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…For example, Rynkiewicz et al [19] reported an average accuracy of ±3.5 years using a wrist bone maturation method, while Chen et al [20] reported an average accuracy of ±3.7 years using a combination of dental and wrist bone maturation. Finally, this paper extends to two indices the methodology proposed in Bucci et al [8], where the best-performing method exhibited an accuracy of ±2.8 years. These findings suggest that the model developed in our study is a promising tool for accurately estimating chronological age in children and adolescents.…”
Section: Discussionmentioning
confidence: 57%
“…The predictive performance of the methodology here presented was compared with that of a single predictor model and a model in which the predictors were considered independent. Given the information found in the existing literature ([1,7,8]), we assumed a segmented relationship with a single breakpoint for the dental maturity index, S, by using a segmented function including one breakpoint [8], and a linear relationship for the hand-wrist maturation index, W. The simulation process is:…”
Section: Appendix A2 Copula Theorymentioning
confidence: 99%
See 1 more Smart Citation